Analysis of Students' Level of Mathematical Understanding Through Online Learning on Binomial Opportunity Distribution Materials - Rifka Usman; Gusniwati; Herlan Sanjaya (Journal of Research on Mathematics Instruction (JRMI), 2020)
This article aims to analyze the achievements of each indicator that measures the mathematical comprehension skills of SMAN 10 Pinrang learners on Binomial Opportunity Distribution materials in online learning through the Ms Teams and WhatsApps applications. This research is a qualitative descriptive research that seeks to analyze the mathematical abilities of learners. Imi's research subjects were students of class XII IPA consisting of 29 students. Data collection methods include tests of the level of mathematical understanding of Binomial Peluan Distribution material. Based on the results of the study, it can be concluded that there are 11 people get a score of 80, 2 people get a score of 90, 9 people who get a score of 95 and 5 people get a score of 100. The overall average is 75.27. This indicates that the level of mathematical understanding of learners is able to choose, use precise formulas and calculations.